2017
DOI: 10.5194/aab-60-61-2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polymorphisms at <i>LEP</i>, <i>CAST</i>, <i>CAPN1</i>, <i>GHR</i>, <i>FABP4</i> and <i>DGAT1</i> genes on fattening performance and carcass traits in Simmental bulls

Abstract: Abstract. The aim of this study was to investigate the effects of single nucleotide polymorphisms (SNPs) at six candidate genes (LEP, CAST, CAPN1, GHR, FABP4 and DGAT1) on fattening performance and carcass traits of Simmental bulls in Turkey. The analysis covered a total of 81 Simmental bulls grown on a private farm that were randomly selected for their fattening period for use in this study. Genotyping was performed using the PCR-RFLP method. The S20T polymorphism at the CAST gene and the G316A polymorphism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 52 publications
(66 reference statements)
1
17
1
1
Order By: Relevance
“…In addition, Pintos and Corva (2011) found significant associations between the same marker with birth weight, weaning weight and live weight recorded at 18 months of age in Angus cattle. Ardicli et al (2017b) reported that homozygous animals for allele G at the CAPN1 G316A marker reached the highest final weight and total weight gain in a shorter fattening period with higher average daily gain in Simmental bulls. Among the factors considered, it is possible that Warner-Bratzler shear force (WBSF) values show an association with LW and that selection for this marker may lead to changes in both traits.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Pintos and Corva (2011) found significant associations between the same marker with birth weight, weaning weight and live weight recorded at 18 months of age in Angus cattle. Ardicli et al (2017b) reported that homozygous animals for allele G at the CAPN1 G316A marker reached the highest final weight and total weight gain in a shorter fattening period with higher average daily gain in Simmental bulls. Among the factors considered, it is possible that Warner-Bratzler shear force (WBSF) values show an association with LW and that selection for this marker may lead to changes in both traits.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the prevalence of homozygous AA animals (85.71%), the superiority of A allele across animals in population was found (A=0.93, K=0.07). Such a low frequency of K allele was reported for various breeds of beef or dual-purpose cattle, including Charolais (Ripoli et al, 2006), Angus (Kaupe et al, 2007), Simmental (Ardicli et al, 2017), and Russian beef cattle (Gorlov et al, 2014). On the other hand, the dairy cattle (Holstein, Jersey) showed much higher frequency of K allele (Kaupe et al, 2004;Casas et al, 2005;Citek et al, 2007).…”
Section: Resultsmentioning
confidence: 75%
“…Carcass traits are alongside fattening performance one of the most important traits in beef industry. It is generally accepted that the beef production is very complex and time-consuming field of the livestock industry (Gorlov et al, 2014;Ardicli et al, 2017). The majority part of traits associated with carcass quality and meat yield is under the control of polygenic inheritance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations